Adherence to Oral Anticancer Therapeutics in the Gynecologic Oncology Population. Issue 6 (December 2020) - Watson, Catherine H.; Fish, Laura J.; Falkovic, Margaret; Monuszko, Karen; Lorenzo, Amelia; Havrilesky, Laura J.; Secord, Angeles Alvarez; Davidson, Brittany A.
Abstract : INTRODUCTION: To gain a better understanding of gynecologic oncology patient adherence to oral anticancer agents through both a cross-sectional survey of adherence and qualitative interviews with patients and clinicians regarding their experience with these medications. METHODS: Eligible participants completed a survey for this cross-sectional study that included an assessment of adherence, distress, quality of life, and health literacy. Any woman taking an oral anticancer agent for a gynecologic malignancy at a tertiary academic medical center for 30 days or more was eligible. Semi-structured qualitative interviews (n=14) were then conducted to explore experiences with oral anticancer agents. We also conducted a qualitative group interview with physicians and nurse practitioners. RESULTS: One hundred women taking oral anticancer agents were enrolled. Fifty-four percent reported perfect adherence to their medication, 21% reported equivocal adherence (demonstrating at least one nonadherent behavior in the previous 7 days), and 25% reported nonadherence (demonstrating more than one nonadherent behavior in the previous 7 days). Qualitative analysis identified five major themes: ease of use compared with traditional therapy; the mental burden of self-administrated medication; perceived importance of the medication; management of side effects; and the desire for consistent physician communication. Common misperceptions expressed in the health care professional interviews included high adherence to oral medications and a belief that cost was the biggest barrier to adherence. CONCLUSION: Almost half of the patients surveyed reported equivocal or nonadherence to their oral anticancer agent. The qualitative interviews identified several important themes, many of which were not recognized by physicians and nurse practitioners. These findings highlight the need for patient and health care professional interventions to improve patient adherence. Abstract : Only 54% of gynecologic oncology patients prescribed oral anticancer agents reported perfect adherence to therapy; reasons for possible nonadherence were variable and nuanced.